Studi Fenomenologis Kebersyukuran Pada Mahasiswa Perguruan Tinggi Swasta Yang Kuliah Sambil Bekerja - Hidayat, Ahmad; Muliadi, Rahmad (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2023)
This study aims to explore the phenomenon of gratitude in private university students who study while working. The qualitative approach used in this study is a phenomenological model. Participants consisted of 4 students studying while working part time and odd jobs. These students expressed their motivation to study while working because of economic demands, looking for experience, to fill their free time and ease the burden on their parents in tuition fees. Participants in this study experienced various obstacles in carrying out activities between college and work so that the coping responses or lifestyle carried out by college students while working were: a) choosing a priority scale, b) dividing study and work time, c) communicating effectively, d ) build friendships, e) maintain health and f) have feelings of shame if they are not able to meet the standards that have been set. Studying while working turns out to lead to positive emotions of gratitude which is a source of strength for them, which can be explained as a result of this study as follows: a) accepting gifts (students get dispensation from the workplace, lecturers, and fellow students), b) realizing the value of gifts (students feel proud because they are more economically independent and ashamed to trouble their parents, c) respect the intention of the giver (trying to finish college and trying to get a bachelor's degree on time as a form of gratitude to Allah for all the life experiences lived and appreciating the gifts of the people around him both materially and immaterial). In addition, these students can feel the benefits of gratitude, including avoiding feelings of envy, hate, anger or greed and feeling happiness through this gratitude experience.